Odnaleźć phronesis w aisthesis. Paul Ricoeur wobec samotności wyboru i działania - Jakubowski, Piotr (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
This article tries to answer the question whether is possible to achieve such a wisdom of situational overview to recognize right way of acting in a situation of tragic moral choice, connected with incertitude and loneliness of decision-making subject. Paul Ricoeur’s Oneself as Another is discussed here as well as its main reference points, that is Aristotle’s Nicomachean Ethics and Kant’s moral doctrine. The solution given by Ricoeur – as it is claimed – is the strongest one, even if insufficient to ultimately eliminate anxiety and incertitude that moral subject is fated to.